2014
DOI: 10.1016/j.bbrc.2014.02.129
|View full text |Cite
|
Sign up to set email alerts
|

H2S relaxes isolated human airway smooth muscle cells via the sarcolemmal KATP channel

Abstract: Here we explored the impact of hydrogen sulfide (H2S) on biophysical properties of the primary human airway smooth muscle (ASM)–the end effector of acute airway narrowing in asthma. Using Magnetic Twisting Cytometry (MTC), we measured dynamic changes in the stiffness of isolated ASM, at the single-cell level, in response to varying doses of GYY4137 (1–10 mM). GYY4137 slowly released appreciable levels of H2S in the range of 10–275 µM, and H2S released was long lived. In isolated human ASM cells, GYY4137 acutel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…A similar smooth muscle relaxant effect of GYY4137 has now been described in a range of tissues including human airway smooth muscle cells via opening of sarcolemma K ATP channels (Fitzgerald et al, 2014), mouse intrapulmonary airways by an effect on intracellular calcium release (Castro-Piedras & Perez-Zoghbi, 2013), pig bladder neck tissues again by opening K ATP channels (Fernandes et al, 2013), pregnant rat myometrial smooth muscle cells (Robinson & Wray, 2012) and in the bovine ciliary artery (Chitnis et al, 2013). Intriguingly, GYY4137 can occasionally, and in defined conditions, exert the opposite effect on blood vessels.…”
Section: Effect Of Gyy4137 On Nonvascular Smooth Musclesupporting
confidence: 57%
“…A similar smooth muscle relaxant effect of GYY4137 has now been described in a range of tissues including human airway smooth muscle cells via opening of sarcolemma K ATP channels (Fitzgerald et al, 2014), mouse intrapulmonary airways by an effect on intracellular calcium release (Castro-Piedras & Perez-Zoghbi, 2013), pig bladder neck tissues again by opening K ATP channels (Fernandes et al, 2013), pregnant rat myometrial smooth muscle cells (Robinson & Wray, 2012) and in the bovine ciliary artery (Chitnis et al, 2013). Intriguingly, GYY4137 can occasionally, and in defined conditions, exert the opposite effect on blood vessels.…”
Section: Effect Of Gyy4137 On Nonvascular Smooth Musclesupporting
confidence: 57%
“…However, GYY4137 exhibited a much slower (~10 min) vasodilation. In a different study, Fitzgerald and co-workers demonstrated the single-cell level relaxation effects of GYY4137 on airway smooth muscle (ASM) (Fitzgerald et al 2014). In this experiment, H 2 S release from GYY4137 in culture media was confirmed by a methylene blue (MB) assay.…”
Section: Gyy4137 and Phosphorodithioate-based Donorsmentioning
confidence: 97%
“…Furthermore, inhibition of endogenous H 2 S production with PPG reduced whole-cell K ATP currents. H 2 S also causes the relaxation of human airway SMCs via stimulating sarcolemmal K ATP channels (Fitzgerald et al 2014). Other studies proved that H 2 S interacts with the SUR subunits of the K ATP channel complex to cause the channel to open, and the sulfhydryl groups located on the extracellular surface of the SUR subunits are potential targets for H 2 S S-sulfhydration (Jiang et al 2010).…”
Section: H 2 S and Smc Relaxation And Contractionmentioning
confidence: 98%